Development and pilot evaluation of the Cognition domain of the Hong Kong Comprehensive Assessment Scales for Toddlers. (19th May 2021) - Leung, Cynthia; Pin, Tamis; Siu, Andrew; Au, Alma; To, Carol; Lo, Sing Kai; Chan, Becky; Lau, Kelly; Ng, Theresa; Chan, Cyrus; Lam, Catherine; Lee, Florence
ABSTRACT: Purpose : To describe the development of the Cognition domain of the Hong Kong Comprehensive Assessment Scales for Toddlers (HKCAS-T). Methods : Participants included 345 toddlers aged 18–41 months, with 258 recruited from Maternal and Child Health Centers (MCHCs) and 87 with cognitive delay recruited from Child Assessment Centers (CACs). They were individually administered the 83-item pilot version by medical practitioners or educational psychologists between 2017 and 2019 in MCHCs and CACs in Hong Kong. Results : Rasch analysis results supported the unidimensionality of the pilot version, after removing six items. Analysis of covariance results indicated that both the 83-item version and the 77-item version could differentiate between children of different age groups, and children with typical development from children with cognitive delay. Internal consistency and interrater reliability were 0.90 or above. Conclusions : The Cognition domain of the HKCAS-T is a promising developmental assessment tool for the assessment of toddlers. Cognition assessment, preschool, Chinese